Interoperability of DRM Systems Exchanging and Processing XML-based Rights Expressions - Guth, Susanne (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2018)
The study deals with the cutting-edge subject of electronic contracts which have the potential to automatically process and control the access rights for (electronic) goods. It shows the design and the implementation of a rights expression exchange framework. The framework allows DRM systems to exchange electronic contracts, formulated in a standardized rights expression language, and thus provides DRM system interoperability. The work introduces a methodology for the standardized composition, exchange and processing of electronic contracts or rights expressions.